Poly(3-hydroxybutyrate)/poly(amine)-coated nickel oxide nanoparticles for norfloxacin delivery: antibacterial and cytotoxicity efficiency. Issue 56 (17th September 2020) - Salahuddin, Nehal; Gaber, Mohamed; Mousa, Maie; Abdelwahab, Mohamed A.
Abstract : PHB/poly(amine)-coated NiO nanoparticles for NOR delivery: antibacterial and cytotoxicity efficiency. Abstract : Sustained release dosage forms enable prolonged and continuous release of a drug in the gastrointestinal tract for medication characterized by a short half lifetime. In this study, the effect of blending polyamine on poly(3-hydroxybutyrate) (PHB) as a carrier for norfloxacin (NF) was studied. The prepared blend was mixed with different amounts of NiO nanoparticles and characterized using FTIR analysis, X-ray diffraction analysis, thermogravimetric analysis, dynamic light scattering, transmission electron microscopy and scanning electron microscopy. It was found that the drug released from the nanocomposite has a slow rate in comparison with NiO, PHB, and PHB/polyamine blend. The highest ratio of NiO content to the matrix (highest NF loading), leads to a slower rate of drug release. The release from the nanocomposites showed a faster rate at pH = 2 than that at pH = 7.4. The mechanisms of NF adsorption and release were studied on PHB/polyamine–3% NiO nanocomposite. In addition, the antimicrobial efficacy of nanocomposites loaded with the drug was determined and compared with the free drug. Inclusion of NiO into PHB/polyamine showed a higher efficacy against Streptococcus pyogenes and Pseudomonas aeruginosa than the free NF. Moreover, the cytotoxicity of PHB/polyamine–3% NiO against HePG-2 cells was investigated and compared with PHB and PHB/polyamine loaded with the drug. The most efficient IC50 was found for NF@PHB/polyamine–3% NiO (29.67 μg mL −1 ). No effect on cell proliferation against the normal human cell line (WISH) was observed and IC50 was detected to be 44.95 and 70 μg mL −1 for NiO nanoparticles and the PHB/polyamine–3% NiO nanocomposite, respectively indicating a selectivity of action towards tumor cells coupled with a lack of cytotoxicity towards normal cells.